AN ANALYSIS OF TEACHING WRITING STRATEGY BY ONLINE DURING COVID-19 PANDEMIC AT SMK PGRI 2 GIRI BANYUWANGI - Ica Cahya Tristiara; Wageyono; Arin Inayah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
This research aimed to know the strategies used and the problems faced by the teachers in teaching writing by online at SMK PGRI 2 Giri Banyuwangi. The scope of this study is to analyze teaching writing by online during covid-19 pandemic at SMK PGRI 2 Giri Banyuwangi and limit only to the strategy used in teaching writing by online during covid-19 pandemic. This study used qualitative research. The subjects of the research are three of English teachers at SMK PGRI 2 Giri Banyuwangi. The instruments used to collect the data is an interview. The technique of data analysis which used in this research is interactive model of analysis from Miles and Huberman. They are: reducing the data, display the data and drawing and verifying conclusion. The finding of the research showed the respodents use two teaching writing strategies during pandemic, those are teacher presentation and self-awareness exercises / tests (Large and Small Group Discussion). The teachers deliver the material using presentation by Zoom and then share and collect the task in Google Classroom. In certain condition, students can come to the school for doing small group discussion with the teachers directly. Therefore, there are three problems faced by teacher during teaching writing by online, there are internet connection, students’ lack of interest and inappropriate teaching strategy.